Development of E-Modules Based on Local Wisdom on Ecosystem Material to Increase Scientific Literacy - Nunung Nurhayati; Dadang Jaenudin; Elly Sukmanasa (STAI Hubbulwathan Duri, 2025)
This study aims to evaluate the validity, effectiveness, and practicality of an E-Module developed based on local wisdom. The research employs the ADDIE development model and includes both limited and expanded trials. The study utilizes a development research (RD) approach, conducting small-scale trials with 10 students and large-scale trials with 26 grade IV students at SDIT Aliya. The validity of the product is assessed through validation tests of the material, media, language, and usage by students and teachers. Effectiveness is measured using pretest-posttest results and analyzed with t-tests. The E-Module was found to be highly valid, with teacher assessments indicating excellent content, presentation, and language appropriateness. Both teacher and student responses in the trials were classified as very good. Effectiveness analysis revealed an N-Gain score of 0.57, indicating a medium improvement. The paired t-test for pretest and posttest results yielded a significant value of 0.00, confirming the effectiveness of the module. The significant improvement in students' scientific literacy suggests that the local wisdom-based E-Module enhances meaningful learning. By connecting the content to students' local identity, the module fosters a deeper understanding of scientific concepts, demonstrating its potential as an effective educational tool. The E-Module based on local wisdom is valid, effective, and practical, leading to a notable improvement in students' scientific literacy.